MOLECULAR DYNAMICS SIMULATIONS OF THE STK630921 INTERACTIONS TO INTERLEUKIN-17A - RIANDONO, FRANSISCUS DEDDY; ISTYASTONO, ENADE PERDANA (International Journal of Applied Pharmaceutics, 2023)
Objective: This research aimed to investigate the stability of the STK630921-Interleukin 17A (IL-17A) complex and to predict important residues that interact during molecular dynamics simulations. Methods: Molecular docking simulations were performed, followed by molecular dynamics (MD) simulations and the free energy of binding calculations using YASARA-Structure. The identification of interacting residues was done using PyPLIF HIPPOS. Molecular docking simulations were performed on the IL-17A binding pocket with the compound 4-[(N-[(4-Oxo-3,4-dihydro-1-phthalazinyl) acetyl] alanyl amino) methyl] cyclohexane carboxylic acid or known as STK630921. The best-docked pose was selected for the 50 ns MD simulations production run. The MD simulations snapshots were then analyzed to see the stability of IL-17A and for the identification of interacting residues, followed by Molecular Mechanics/Poisson–Boltzmann and surface area (MM/PBSA) analysis for the free energy of binding calculations. Results: STK630921 is relatively able to stabilize IL-17A. Important interaction residues identified during the MD simulations were: Thr35(A), Pro37(A), Tyr62(A), Pro63(A)(B), Ile66(A)(B), Trp67(A), Ile96(A)(B), Val98(A)(B) and Val117(A)(B). Conclusion: STK630921 disrupts the interaction of IL-17A to its receptor by binding and stabilizing IL17A.